Age‐friendly interventions in rural and remote areas: A scoping review. (7th July 2022) - Montayre, Jed; Foster, Jann; Zhao, Ivy Yan; Kong, Ariana; Leung, Angela Y. M.; Molassiotis, Alex; Officer, Alana; Mikton, Christopher; Neville, Stephen
Abstract: Objectives: In 2007, the World Health Organization published a guide on age‐friendly cities. However, little is known about interventions that have been implemented to promote age‐friendly communities in rural and remote areas. This paper presents the findings from a scoping review undertaken to locate available evidence of interventions, strategies, and programs that have been implemented in rural and remote areas to create age‐friendly communities. Methods: This scoping review used the Joanna Briggs Institute (JBI) methodology. Results: A total of 219 articles were included in this review. No intervention studies were referred to as 'age‐friendly'. However, there were interventions (mostly healthcare‐related) that have been implemented in rural and remote areas with older people as participants. There were also non‐evaluated community programs that were published in the grey literature. This review identified the common health interventions in older people and the indirect relevance to the WHO age‐friendly framework domains in rural and remote contexts. Conclusions: The eight age‐friendly domains were not explicitly utilised as a guide in the development of interventions for older people in rural and remote settings. Implementation of age‐friendly interventions in rural and remote areas requires a multisectoral approach that is tailored to address the specific needs of individual communities. Age‐friendly interventions also need to consider socio‐ecological factors to adequately and holistically address community needs and ensure long‐term sustainability.